Age at onset in Huntington's disease and methylation at D4S95. Issue 3 (March 1993) - Reik, W; Maher, E R; Morrison, P J; Harding, A E; Simpson, S A
Abstract : Age at onset in Huntington's disease (HD) is variable and is influenced by parental sex, paternal age, and genetic background. Several recent models have tried to explain this variable expressivity by invoking parental imprinting and related aspects of epigenetic inheritance. Some of these mechanisms may result in variable DNA methylation at or near the HD gene. We show here that methylation at D4S95, a locus tightly linked to the HD gene, is highly variable. A comparison between patients with early onset HD, late onset HD, and normal controls showed no significant correlation between methylation and age at onset. However, we found a significant association of the age of the patient with demethylation at D4S95. Older persons tend to have lower levels of methylation at this locus. This observation is of interest with regard to studies that show an effect of paternal age, or more generally of 'ageing genes', on age at onset in HD.